The Development of the Science of Theology from Simple to Complex Questions between it and Philosophy - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
The science of theology faced various stages from its emergence to maturity by its development at the levels of content and methodology. It was launched initially by asking questions in the religious text related to the belief of believers. Also, its launching were linked with the events that were dictated by the successive social and political changes. The effects of scholars were directed to fortify and defend the faith, trying to preserve the specifics of the content and methodology of this science. In contrast, the presence of foreign cultures in the field of Islamic thought affected them inevitably, especially Greek philosophy.Although researchers of theology were reticent in accepting the intellectual mixing between philosophy and speech but they even alienated from it. However, in the end he imposed himself a forbidden marriage between two different tributaries in Islamic thought. In this context, I am doing this research as an attempt to trace the development of speech science and its formation through three major topics. The first is about the emergence of the science of speech through simple questions from within the text as well as the initial external influence represented in behavior. The second is concerned with the development of disciplined theory for its fundamental terminology and specifics. The third one is related to the methodology of blending and communication with philosophy, wondering about the extent of this forbidden marriage and its limits. This is somewhat obvious through an extrapolation of historical events and mental transformations in the internal structure of the contents of science of theology and methods.